An analysis of the changing role of systems librarians. Issue 2 (19th June 2017) - Ratledge, David; Sproles, Claudene
Abstract : Purpose: The purpose of this paper is to analyze technology-related librarian advertisements to examine the changing role of the systems librarian in today's modern, technology-filled libraries. Design/methodology/approach: The authors examined 70 advertisements for technology-focused librarians posted on ALA's JobList in 2014. The ads were examined for area of focus and required knowledge and experiences. Findings: The ads revealed three main areas of focus: traditional systems, digital initiatives, and web services. In addition to traditional computer and library systems skills, employers were seeking candidates with project management, digital collection, customer service, technology implementation, and problem solving skills and experience. Practical implications: This study highlights how the adoption and expansion of library technology has altered the roles and responsibilities of systems librarians. Instead of solely focusing on maintaining library databases and ILSs, technology librarians have branched out and become more integrated within the library. Originality/value: This study has implications for those entering the library field and LIS programs, as well as gaining insight into the expanding role of technology librarians today's library.